Effects on thrombocytic hemostasis of a new derivate indolinone - Bykov, VV; Serebrov, V Yu; Udut, VV; Udut, EV; Fisenko, VP (Bangladesh Journal of Medical Science, 2019)
Objective. Specific activity of an antiplatelet drug of indolinone series (codenamed DI) was studied in vitro in a model of ADP-induced platelet aggregation in vitro and in vivo in a model of streptozotocininduced diabetes mellitus in rats. Material and Methods. Acetylsalicylic acid and dipyridamole were used as reference drugs. In vitro tests have demonstrated that DI exhibits antiplatelet activity in a wide range of concentrations (0,75×10-6 – 1.5×10-5 М, р<0,05), being comparable to acetylsalicylic acid and dipyridamole. In vivo tests have demonstrated dose-dependent antiplatelet activity of DI in doses of 2,5 – 20 mg/kg (21-14 %). Results and Discussion.Increasing the dose of DI above 10 mg/kg doesn’t increase its antiplatelet activity. After multiple oral administration to rats with streptozotocin-induced diabetes mellitus in 10 mg/kg dose, DI has exhibited antiplatelet activity, reducing the platelet aggregation rate to that of the control group (р<0,05). Conclusion. Thus, DI isapromisingcompound for furtherdevelopmentof an antiplatelet drug with new mechanism of action Bangladesh Journal of Medical Science Vol.18(3) 2019 p.574-576